Uterine Tachysystole with Prolonged Deceleration Following Nipple Stimulation for Labor Augmentation - Narasimhulu, D.M.; Zhu, L. (Kathmandu University Medical Journal, 2017)
Breast stimulation for inducing uterine contractions has been reported in the medical literature since the 18th century. The American college of Obstetricians and Gynecologists (ACOG) has described nipple stimulation as a natural and inexpensive nonmedical method for inducing labor. We report on a 37 year old P2 with a singleton pregnancy at 40 weeks gestation who developed tachysystole with a prolonged deceleration after nipple stimulation for augmentation of labor. Initial resuscitative measures, including oxygen by mask, a bolus of intravenous fluids and left lateral positioning, did not restore the fetal heart rate to normal. After the administration of Terbutaline 250 mcg subcutaneously, the tachysystole resolved and the fetal heart rate recovered after five minutes of bradycardia. Most trials of nipple stimulation for induction or augmentation of labor have had small study populations, and no conclusions could be drawn about the safety of nipple stimulation, though its use is widespread. While there have been a few reports of similar complications during nipple stimulation for contraction stress testing, there are no previous reports of tachysystole with sustained bradycardia following nipple stimulation for labor augmentation. In this report, we draw attention to the dangers of nipple stimulation so that providers will be aware of this potential complication.